ANALISIS KUALITAS PELAYANAN DAN CITRA MEREK DI RESTORAN SAMBAL BAKAR - Fegi Atasyaningrum; Tito Pratama (JURNAL MENATA, 2026)
This study aims to analyze customer experiences regarding service quality and to identify the factors shaping the brand image of Sambal Bakar Restaurant in Batam. The rapid growth of the culinary industry and viral marketing creates high customer expectations, yet operational challenges during peak hours often lead to inconsistencies in service delivery. A qualitative descriptive approach with a case study strategy was employed. Data were collected through in-depth interviews with the owner, two employees, and six loyal/new customers, non-participant observation, and documentation, including online reviews. The analysis used the Miles and Huberman interactive model and SWOT analysis. The findings reveal that overall customer experience with service quality is positive, particularly in tangible aspects (authentic hot cobek presentation) and assurance (friendly staff). However, significant weaknesses exist in responsiveness and reliability during peak loads, characterized by wait times of 15-20 minutes and order inaccuracies, creating a SERVQUAL gap between viral hype and actual service. Brand image is strongly formed by three factors based on Keller's theory: strength of association (authentic spicy taste), favorability (affordable, humble atmosphere), and uniqueness (viral TikTok sambal grilling innovation). The SWOT analysis concludes that the restaurant's sustainable brand equity heavily depends on improving operational consistency to align service delivery with its strong brand promise, preventing customer dissonance and negative word-of-mouth.